Perkembangan Kepribadian Anak Dengan Pola Asuh Permisif, Over Protektif Dan Otoritatif - Nur Khamim (Journal of Education and Religious Studies, 2021)
Children are the future of the nation. The child's development period is an important time in determining the character of the child. The behavior and actions of parents to children become a pattern of foster care that plays an important role in shaping their character. Activities and backgrounds of parents can form a pattern of foster care applied to their child. The form of foster care patterns has its own impact, both permissive, over protective and authoritative foster care patterns. Through quantitative research method with 100 respondents obtained that the three foster care patterns are related to the development of children's personality. All three have significant influence.